Primary trigeminal neuralgia and the role of pars oralis of the spinal trigeminal nucleus. (March 2017) - Peker, Selcuk; Sirin, Alperen
Abstract: Trigeminal neuralgia is a painful condition that causes great discomfort. Although this disease has been known for more than 1000 years, there is still no consensus on its underlying mechanism or treatment. Many hypotheses have been reported to explain the cause and nature of trigeminal neuralgia. These include theories about peripheral mechanisms and central mechanisms. We put forward a new hypothesis that trigeminal neuralgia is associated with the pars oralis of the spinal trigeminal nucleus (POSTN). The main basis for this is the close similarity between trigger point distribution and the area of influence of the POSTN. We also highlight that the areas of influence for the trigeminal nerve divisions do not match the trigger point distribution; therefore, peripheral theories should be further investigated.